Girl, interrupted - Kaysen, Susanna, 1948- (New York : Vintage Books, 1994)
The author describes her two-year stay at a psychiatric hospital renowned for its famous clientele and for its progressive methods of treatment.
Originally published: New York : Turtle Bay Books, 1993.
Library Journal.
Wilson's Public Library.
Wilson's Senior High School.
Adult
Keywords: Kaysen, Susanna, -- 1948- -- Mental health; Kaysen, Susanna, -- 1948-; Psychiatric hospital patients -- Massachusetts; Psychiatric hospital patients